2019
DOI: 10.3233/nre-182665
|View full text |Cite
|
Sign up to set email alerts
|

Circadian activity rhythm and fragmentation are associated with sleep-wake patterns and sleep quality in patients with stroke

Abstract: BACKGROUND: Activity levels and disturbances of the sleep-wake pattern affect health and quality of life and need to be further explored in patients with stroke. OBJECTIVE: To evaluate activity levels and their association with sleep-wake patterns in patients with stroke. METHODS: Ten adults with (51 ± 6 years) and 10 without stroke (52 ± 7 years) participated in the study; they were matched on age, sex and educational level. Neurological status, motor function, sleep quality, and activity levels were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This may be caused by different epidemiological patterns of stroke in different regions. It has been shown that younger age and less likelihood of low physical activity were the characteristics of stroke in Asia, [26,27] which Ho et al, [12] Hongkong Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Khazaei et al, [13] Iran Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Sonmez et al, [15] Cyprus Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Pereira et al, [16] Brazil Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Kasai et al, [18] Japan Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Zhao et al, [20] China Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Nguyen et al, [24] Vietnam Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 de Oliveira et al, [23] Zhang et al, [14] China 1 1 0 0 2 1 0 1 6 He et al, [19] China 1 1 0 0 2 1 0 1 6 Fan et al, [21] China 1 1 0 1 2 1 1 1 8 Xiao et al, [17] China 1 1 0 0 2 1 0 1 6 Brutto et al, [22] may be related to lower prevalence of poor sleep quality. This was consistent with a previous review regarding the association between physical activity and quality of sleep.…”
Section: Crossmentioning
confidence: 99%
“…This may be caused by different epidemiological patterns of stroke in different regions. It has been shown that younger age and less likelihood of low physical activity were the characteristics of stroke in Asia, [26,27] which Ho et al, [12] Hongkong Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Khazaei et al, [13] Iran Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Sonmez et al, [15] Cyprus Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Pereira et al, [16] Brazil Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Kasai et al, [18] Japan Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Zhao et al, [20] China Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 Nguyen et al, [24] Vietnam Yes Yes Yes Yes Unclear Unclear Yes Yes Unclear Yes No 6 de Oliveira et al, [23] Zhang et al, [14] China 1 1 0 0 2 1 0 1 6 He et al, [19] China 1 1 0 0 2 1 0 1 6 Fan et al, [21] China 1 1 0 1 2 1 1 1 8 Xiao et al, [17] China 1 1 0 0 2 1 0 1 6 Brutto et al, [22] may be related to lower prevalence of poor sleep quality. This was consistent with a previous review regarding the association between physical activity and quality of sleep.…”
Section: Crossmentioning
confidence: 99%
“…Circadian rhythm disruption is both a risk factor and consequence of stroke. 15 One study 16 found that stroke patients exhibited more fragmented RAR compared to matched non-stroke controls. Preclinical studies have identified mechanisms in which circadian rhythm disruption interferes with key functions in stroke pathophysiology (eg, neurogenesis, angiogenesis, and immune response) and impairs stroke recovery.…”
Section: Introductionmentioning
confidence: 99%
“…19,[21][22][23][24][25][26] In addition, studies have revealed altered circadian and sleep-wake patterns (via RARs) in patients with stroke. [27][28][29] Given that increased risk for dementia, depression, disability, and mortality are wellestablished long-term adverse outcomes in post-stroke survivors, 30,31 understanding the relationship between altered RARs and such post-stroke outcomes is vital for prevention and long-term management.…”
Section: Introductionmentioning
confidence: 99%